Peran Orang Tua dalam Meningkatkan Kualitas Pendidikan Anak - Sukmawati, Anis; Putri, Mega Silviya; Ningrum, Dewi Chintia Cahya (ANWARUL, 2023)
This article discusses the role of parents in improving the quality of children's education. Through their role as first educators, creators of a supportive learning environment, active school partners and role models of educational values. Parents have great potential to help their children achieve success in their education. However, there are some parents who do not have an awareness of the importance of their contribution to their children's learning process. Parents' awareness of the importance of their contribution is expected to encourage collaborative efforts between home and school to get perfect or maximum results in the learning process.